Practicality and Effectiveness of Activity-based Worksheets with the ExPRession Learning Model to Train Hands-on Activities on Newton's Law - Tria Anisa; Kartini Herlina; Viyanti Viyanti (Jurnal Ilmiah Pendidikan Fisika, 2024)
This research aims to determine the practicality and effectiveness of worksheets based on the ExPRession learning model to train direct practical activities on Newton's laws. The samples are classes of X Science 4 and X Science 5 at SMAN 1 Gadingrejo in the 2022/2023 academic year. The research design uses the Pretest-Posttest Control Group Design. Applying worksheets with the ExPRession learning model in physics learning effectively trains students' activity skills. This is proven by the results of learning implementation using the ExPRession learning model, reaching 87.30%, and the assessment of students' Hands-on Activity, reaching 78.35%. The results of hypothesis testing also show a higher difference in students' practical activity skills between classes that apply worksheets based on the ExPRession learning model in physics learning. Based on the research results, it was found that implementing activity-based worksheets with the ExPRession learning model impacted training students' hands-on activity skills. This is because learning using various forms of representation can help students' understanding of concepts when solving physics problems. Students are more enthusiastic if the physics learning process is accompanied by simple, practical work. It was concluded that using worksheets based on the ExPRession learning model was effective for training students' hands-on activity skills.